Altered Sex Ratios in Offspring of U.S. Submariners Urban Legend or Fact – Do Submariners Have More Daughters?. Issue 7 (24th January 2019) - Kramer, Kathleen; Raiciulescu, Sorana; Olsen, Cara; Hickey, Kimberly; Ottolini, Martin
Abstract: Introduction: There is a widespread and long-held belief in the submarine community that submariners father more daughters than the general population. The U.S. Sex Ratio at birth (males/females) has remained around 1.05 since the early 2000s. Limited evidence exists that certain environmental exposures including chemicals, heavy metals, radiation and g-forces may influence sex ratio at birth. A reduction in male births in a population has been associated with lower male fertility. A 1970 single site study showed a higher ratio of female offspring in personnel serving aboard U.S. Navy nuclear submarines than the general population. A 2004 study concluded that this was probably not true. However, this study was small, and did not evaluate the difference between children conceived during sea duty versus shore duty. They did note a higher chance of female offspring correlated with a longer time in the community, as well as an increased ratio in sonar technicians. These findings warrant further investigation. Methods: An electronic survey was e-mailed to submariners, after receiving required IRB and Navy approvals. Participants were asked birth year, year they entered submarine service, and how many children they had. For each child they were asked sex, child's birth year, mother's birth year, and whether they were on sea duty or shore duty at the time of conception. Those who were on sea duty at the time of conception were asked what their job was, where they were stationed and what type of submarine they were on. Those who were on shore duty at the time of conception were asked whether they were in contact with submarines on a regular basis, whether they were officer or enlisted, and what region they were stationed in for shore duty. Results: Four thousand eight hundred responses were received with a total of 6, 958 children included in the analysis. Respondents had a SR of 0.95 compared to 1.05 U.S. population in 2015 ( p < 0.0001). Submariners on sea duty had a SR of 0.88 compared to 1.02 on shore duty ( p = 0.007). Those who had regular submarine contact on shore duty had a SR of 0.72 compared to 1.17 in those who did not ( p < 0.001). Geographical location during shore duty did show differences that were statistically significant ( p = 0.018). Geographical location during sea duty did not show significant differences. No significant differences were seen for paternal age, maternal age, job during sea duty, type of submarine assigned to or time in community. Conclusion: The submariners surveyed reported greater numbers of daughters than the general population, especially when on sea duty or in regular contact with submarines during shore duty. Further study should be done to confirm results and explore possible etiologies of differences in sex ratio.